Current placenta previa management and outcome in a rural tertiary care centre - Sood, Reena; Sharma, Swati; Nagpal, Madhu; Arora, Madhurima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The reported incidence for placenta previa averages 0.3% or 1 case in 300 to 400 deliveries. Multiparity, advanced maternal age, cigarette smoking, previous caesarean delivery, history of abortions or uterine surgical procedures are some of the risk factors contributing to the development of placenta previa. Massive obstetrical haemorrhage in placenta previa is associated with severe maternal morbidity and mortality. A significant number of mothers can be saved if right approach of management is followed in placenta previa. Methods: The present case study is a retrospective analysis carried out in a tertiary care centre to study the risk factors and maternal and perinatal outcome in cases of placenta previa. The study included antenatal patients diagnosed as placenta previa on sonography at or >26 weeks of pregnancy. Data was compiled and statistically analysed. Results: Incidence of Placenta Previa in our study was 0.54%. 73.2% patients had history of previous cesarean sections. 53.6% patients were referred from outside. 98.2% patients delivered by caesarean section. Obstetric hysterectomy was required in 3.5% of total cases. 10.7% cases required the ICU admission after delivery. There was no maternal mortality in the study group. The mean gestational age at delivery was 35±2.4weeks. The mean APGAR at 5 min was 9±2.2. Conclusions: Increasing rates of caesarean sections in present era indicate that incidence of Placenta Previa is expected to rise. Good antenatal care, availability of emergency obstetric services, infrastructure, blood bank facility, HDU and ICU care and NICU services can improve maternal and neonatal outcome.